Évolution du système alimentaire haut-alpin - Aurélie Rousselot-Pailley (Revue d'ethnoécologie)
The mountain population living on the territory of the « Pays des Écrins » (department of Hautes-Alpes, France), today very heterogeneous, present a way of life which satys within modernity but still transporting ancient foodways that we can identify in the history of these rural societies. Knowledge and analysis of middle, socioeconomic and family organization allow us to definite the strategies of transmission of food habits, supply and working of the natural environment.During my research, a hundred of semi-aimed discussions were driven with subjects of 20 and more years old, allowing an « inter-generation » approach of food practices. At first, the crossroads of the existent data of the study of a corpus of archives and discussions led with « ancient » allowed us to represent the environmental, agrarian and food contexts of the local population since the beginning of the 19th century. And thus, to identify the markers of transformation of food practices (economy of subsistence versus tourist economy; auto-production versus consumption of outside products, etc).Then, our interest turned on the evolution of strategies of supply still marked by peculiarities linked to hilly environment (picking, hunt, gardening, the orchard, animal husbandry, typical dishes, modes of conservation). This are besides these peculiarities, claimed as markers of local identity, which make the object of a transmission between generations and between social groups. To finish, we will see how certain practices survive and integrate with a feeding regulated by the seasons, so determinating in this kind of environment.